Back Matter Vol 15 No 2, 2023 - Indonesian Journal of Social Sciences (Indonesian Journal of Social Sciences, 2023)
The back matter contains guidelines for authors, index of authors, index of subjects, and a back cover of volume 15 issue 2 (2023)